Stress Mastery : the Art of Coping Gracefully. - Brucato, Laurel; Brucato, Dominic; Abascal, Juan R. (Job Skills Neteffect Ser., 2000)
The creators of a state- of-the-art stress management center combine their decades' of clinical psychology experience to present a complete and concise volume on stress management in the workplace. Their approach incorporates a reader-friendly style with proven exercises and techniques designed to teach readers how to maximize effectiveness and deal with workplace stress. The text includes an introduction to stress, the three phases of the authors' master strategy, as well as a focus on workplace stress mastery and psychotechnologies. For students, workers and the general public interested in stress management techniques.